Making a 21st century constitution playing fair in modern democracies - Vibert, Frank (Edward Elgar Publishing, 2018)
"Democratic governments are increasingly under pressure from populists, and distrust of governmental authority is on the rise. Economic causes are often blamed. [This book] proposes instead that constitutions no longer provide the kind of support that democracies need in today's conditions, and outlines ways in which reformers can rectify this. [The author] addresses key sources of constitutional obsolescence, identifies the main challenges for constitutional updating and sets out the ways in which constitutions may be made suitable for the the 21st century. The book highlights the need for reformers to address the deep diversity of values in today's urbanized societies, the blind spots and content-lite nature of democratic politics, and the dispersion of authority among new chains of intermediaries."--Back cover.